"Power ranking" professional circuit eSports teams using multi-criteria decision-making (MCDM) - Pradhan, S.; Abdourazakou, Y. (Journal of Sports Analytics, 2020)
The utilisation of performance criteria to determine power rankings of various teams is useful for a vast number of audiences in many traditional sports, such as soccer, football, baseball, basketball, hockey, and the like. With market hyper-competition and viewership growth in the digital sector of eSports and related professional video gaming, the usage of performance evaluation in the scholarly literature is relatively scant. Thus, the current study provides a performance assessment and ranking structure in eSports. Applying a hybrid technique developed by previous research involving a series of Multi-Criteria Decision-Making (MCDM) tools, those being: Grey Relational Analysis (GRA), Simple Additive Weighting (SAW), and the Technique for Order Preference by Similarity to the Ideal Solution (TOPSIS), this study develops power rankings for professional teams in the popular multiplayer online battle arena (MOBA) game, Defense of the Ancients (Dota ) 2 . Further analyses offer a comparison of the produced ranking structure to other metrics commonly used in eSports evaluation, such as Elo and Glicko ratings. The findings of this study offer implications for players, teams, performance analysts, oddsmakers, consumers, among others. Recommendations and future directions of this research are also provided.